2011
DOI: 10.1002/tox.20556
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C coadministration augments bisphenol A, nonylphenol, and octylphenol induced oxidative damage on kidney of rats

Abstract: The aim of this study was to investigate whether bisphenol A (BPA), nonylphenol (NP), and octylphenol (OP) induce oxidative stress on the kidney tissue of male rats and whether coadministration of vitamin C, an antioxidant, can prevent any possible oxidative stress. The Wistar male rats were divided into seven groups, including control, BPA, NP, OP, BPA+C, NP + C, OP +C. BPA, NP, and OP (25 mg/kg/day) was administered alone; vitamin C (60 mg/kg/day) was administered along with BPA, OP, and NP to the rats for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…ALP is released in blood stream when liver is damaged or when there is biliary obstruction (Kako et al, ). Korkmaz et al () have also reported alteration in LFT markers as a result of exposure to EDCs such as BPA, nonylphenol, and octylphenol.…”
Section: Discussionmentioning
confidence: 96%
“…ALP is released in blood stream when liver is damaged or when there is biliary obstruction (Kako et al, ). Korkmaz et al () have also reported alteration in LFT markers as a result of exposure to EDCs such as BPA, nonylphenol, and octylphenol.…”
Section: Discussionmentioning
confidence: 96%
“…46,47 Microvascular processes such as those which have been identified in laboratory studies of BPA 48 that lead to low-grade albuminuria may develop over time, and so the cross-sectional association of urinary BPA with increased low-grade albuminuria does not necessarily support causation, even when consistent with growing laboratory evidence. 24,25 Even if earlier life exposures are biologically more plausible, recent evidence suggests that BPA may be stored in fat, 4951 increasing plausibility that current urinary BPA represents earlier, or more chronic, exposures. If current uBPA is a “noisy” index of early exposure, our estimates of association should be biased towards the null.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Given that BPA is a potential contributor to physiologic processes that increase cardiometabolic risk, and since individuals with increased cardiovascular risk have increased albuminuria, 26,27 BPA exposure may be associated with low-grade albuminuria. The only study which has evaluated this possibility examined 3,055 Chinese adults living in the Shanghai region, and identified uBPA as an independent determinant of the extent of low grade albuminuria (albumin:creatinine ratio <30 mg/g), with 23% increased odds for the highest quartile of albuminuria in the highest urinary concentration BPA quartile compared to the lowest quartile.…”
Section: Introductionmentioning
confidence: 99%
“…However, BPA (25 mg/kg) induces nephrotoxicity by increasing oxidative stress in the kidney [Korkmaz et al 2011] and causes an increase in the BUN and creatinine levels in rats treated with BPA (30 mg/kg/day) for one week [Helal et al 2013]. The BUN and creatinine ratio can be used to assess kidney injury and toxicity.…”
Section: Discussionmentioning
confidence: 99%